(untitled) (Revista Argentina de Cirugía, 2021)
Background: The first cholecystectomy was performed by Carl Langenbuch in July 1882. Erich Mühe performed the first laparoscopic cholecystectomy in 1982. Objectives: The aim of this study was to evaluate morbidity and mortality associated with cholecystectomy performed by residents in our service. Methods: We conducted a retrospective cross-sectional study. The information was retrieved from the medical records and operating room records of patients undergoing surgery at the Hospital José Ramón Vidal between January 2012 and January 2015. A total of 1870 cholecystectomies were performed: 1292 (69.1%) were laparoscopic procedures and 578 (30.658%) by conventional approach. All procedures were started and completed by resident physicians under the strict supervision of a staff physician or chief resident. Results: 1203 (64.33%) patients were women and 667 (35.66%) were men. Ten patients (0.77%) required conversion. Morbidity was 0.53% (10 patients) and mortality was 0.05% (one patient). Secondyear residents performed 240 (12.83%) procedures, third-year residents performed 1016 (54,33%) and fourth-year residents 311 (16.63%). After surgery, 1881 (96.8%) patients remained hospitalized for 24 hours and hospital stay duration was of two days in 59 (3.15%) patients. Conclusions: Conventional and laparoscopic cholecystectomy are of great importance for the comprehensive training of residents in surgery: therefore, they constitute a procedure that can and must be performed by them, with appropriate supervision of a staff physician in adequate residency programs.